ANIMASI 3D SEBAGAI MEDIA PROMOSI ITB STIKOM BALI 3D ANIMATION FOR PROMOTIONAL MEDIA ITB STIKOM BALI - Ketut Gus Oka Ciptahadi (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2019)
ABSTRACTIn marketing introducing the STIKOM Bali ITB campus to the wider community, the ITB campus STIKOM Bali already has several media information such as company profile videos, live shot advertisements, brochures and billboards. And the marketing team also uses several social media that are often used by the community. Like Facebook and YouTube Instagram. Although it already has a fairly complete information media coupled with the use of social media. ITB STIKOM Bali still needs a medium of information that provides interesting and unique visuals such as the use of animation. Seeing these problems, in this study the author wants to make a medium of information in the form of 3-dimensional animation that can provide visualization results to be more because with media using 3D animation can provide better and more interesting visual results to the community. In completing this study the authors conducted 3 approaches, first with the research and development (R & D) method. plus 2 approaches in the animation production stage. That is the use of motion blur and the addition of CGI effects. And the results of these products will be tested for feasibility using the Black box testing method.Keywords: 3D, Animation, Multimedia, Research and DevelopmentABSTRAKDalam pemasaran memperkenalkan kampus ITB STIKOM Bali pada masyarakat luas, kampus ITB STIKOM Bali sudah memiliki beberapa media informasi seperti video company profile, iklan live shot, brosur dan baliho. Serta tim pemasaran juga memanfaatkan beberapa social media yang sering digunakan oleh masyarakat. Seperti instagram facebook dan youtube. Walaupun sudah memiliki media informasi yang cukup lengkap ditambah dengan pemanfaatan social media. ITB STIKOM Bali masih membutuhkan sebuah media informasi yang memberikan visual yang menarik dan unik seperti penggunaan animasi. Melihat permasalahan tersebut, pada penelitian kali ini penulis ingin membuat sebuah media informasi berupa animasi 3 dimensi. Dikarenakan dengan media informasi menggunakan animasi 3D dapat memberikan hasil visualisasi yang lebih baik, menarik dan unik kepada para masyarakat. Dalam meyelesaikan penelitian ini penulis melakukan 3 pendekatan, pertama dengan metode research and development (R&D). ditambah 2 pendekatan dalam tahap produksi animasi. Yaitu penggunaan Motion Blur serta penambahaan effect (CGI) Computer Ganerated Imagery. Dan hasil dari produk tersebut akan diuji kelayakannya dengan menggunakan metode Black box testing.Kata kunci: 3D, Animasi, Multimedia, Research and Development